2012
DOI: 10.1016/j.apsusc.2012.06.054
|View full text |Cite
|
Sign up to set email alerts
|

Unusual pattern formation on Si(100) due to low energy ion bombardment

Abstract: In this paper evolution of silicon surface topography, under low energy ion bombardment, is investigated at higher oblique incident angles in the range of 63⁰-83⁰. Si(100) substrates were exposed to 500 eV argon ions. Different surface morphology evolves with increasing angle of incidence. Parallel-mode ripples are observed up to 67⁰ which undergo a transition to perpendicular-mode ripples at 80⁰. However, this transition is not a sharp one but undergoes a series of unusual pattern formation at intermediate an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
26
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 27 publications
3
26
1
2
Order By: Relevance
“…In particular, the existence of a nonzero critical angle, as depicted in Fig. 2, has been also confirmed by other groups working in the low energy range [55][56][57][58]. In general, as shown in the AFM images of Fig.…”
Section: Low-energy ( < 10 Kev)supporting
confidence: 67%
See 1 more Smart Citation
“…In particular, the existence of a nonzero critical angle, as depicted in Fig. 2, has been also confirmed by other groups working in the low energy range [55][56][57][58]. In general, as shown in the AFM images of Fig.…”
Section: Low-energy ( < 10 Kev)supporting
confidence: 67%
“…For instance, see the morphology in . This stage has been recently investigated by Basu et al [57,69]. They found, in analogy with the case of mediumenergy ion bombardment (see Section 3.1.2), that shadowing effects are playing a critical role for the development of such morphology.…”
Section: Low-energy ( < 10 Kev)mentioning
confidence: 98%
“…In experiments in which the ion beam is reasonably close to grazing incidence, the surface frequently develops a terraced form at the late stages of its time evolution [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. A height profile taken along the projected ion direction is not sinusoidal.…”
Section: Introductionmentioning
confidence: 99%
“…In plasma etching, the ion reflection was taken into account in continuum models and MC simulations for feature profile evolution, usually assuming specular reflection from feature sidewalls, to reproduce microtrenches formed at the corner of the feature bottom; 57-65 a few plasma beam and MC studies of Sawin et al suggested the importance of the effects of ion reflection on surface roughening and rippling; 5,25,[31][32][33] the ion reflection was also suggested as a possible explanation for the evolution of surface roughness during pulsed plasma etching. 28 In IBS, Hauffe suggested that the coarsening of terrace-like (or sawtooth-like) ripple structures is caused by reflected ions that re-impinge on the adjacent facets, 53 which was supported in several experiments [66][67][68][69] while not in some other experimental 70 and continuum model 71 studies; Bradley and Harper gave little more than comments on the effects of ion reflection on the ripple formation, in their pioneering theoretical study based on continuum equations; 40 a few classical molecular dynamics (MD) simulations were concerned with the step-edge sputter yields at high off-normal ion incidence arising from the ion reflection and re-impingement and with their effects on the ion surface channeling and ripple formation thereat. [54][55][56] We have investigated surface roughening and ripple formation during Si etching in Cl-based plasmas: 7,72-78 our MC-based three-dimensional atomic-scale cellular model (ASCeM-3D), mechanistically including the effects of ion reflection, simulated the roughening and rippling in response to ion incidence angle θ i .…”
Section: Introductionmentioning
confidence: 85%